Filsafat Ekonomi Islam (Sebuah Tinjauan Teoritis) - Alief, Alief Anshari (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
Islamic economic philosophy lies in humans with God, nature and other humans. This philosophical dimension is what differentiates Islamic economics from the economic systems of capitalism and socialism. The aim of this research is to examine Islamic economic philosophy in terms of three important parts, namely ontology, epistemology and axiology in Islamic economics. This article was written using a literature study method with a qualitative descriptive approach. The primary data used in this research is data taken from references related to the discussion theme, both from books and journals. The conclusion shows that in Islamic economics, there are normative values ​​which are unique in looking at all existing phenomena and problems so that these normative values ​​also become an important signal to present them in all human economic activities. Thus, Islamic economic philosophy becomes the main basis for humans in meeting their daily needs because all economic activities must go through verification of truth based on rationality and revelation.